Application de Ia methode de reanalyse aux assemblages colles - Cheik, Mohammed; Loredo, Alexandre; Aivazzedeh, Shahram (European Journal of Computational Mechanics, 1997)
This paper describes a reanalyse method which enables repetitive calculation times to be reduced. Comparison with complete analysis duration using the finite element method is given. In this method the conditions of stress continuity at the interface of heterogeneous structures were imposed. The results were compared with those calculated by the mixed finite element. Reanalysis was applied to the case of bonded joints.